Carboxymethylation Of Cellulose From Kenaf (Hibiscus Cannabinus L.) Core For Hydrogel Production - Palle, Ismawati (2008)

(untitled)
Kenaf is known as fast growing species which is planted mainly for bast fibre which have been used as an alternative raw material for particleboard, medium density fibreboard or pulp and paper industry. On the contrary, the core of kenaf stem which is consist of straw-like and short-length fibres cannot be used exclusively in particleboard and pulp paper industries due to low strength and dimensional stability. Thus, and alternative usage has to be researched. Since kenaf core have relatively high amount of holocellulose, low lignin content and is highly absorbent, these properties make kenaf core a potential material for producing carboxymethyl cellulose (CMC) in hydrogels. This study comprised three main aspects: 1) Evaluation of the basic properties of kenaf core fibres, 2) Carboxymethylation of the kenaf core and 3) Formation of hydrogel from the carboxymethylated kenaf core.The evaluations of chemical and physical properties of kenaf core fibres were conducted prior to the carboxymethylation process. The samples for fibre morphology and chemical analyses of the kenaf core were prepared from macerized and mechanically refined fibres, respectively. All the chemical analyses were conducted using fibre of 40-mesh size (425 μm size) whilst for fibre morphology (fibre length, fibre diameter, lumen diameter and cell wall thickness) match stick kenaf core samples were used. The study indicates that kenaf core comprises approximately 50.6% alpha-cellulose, 27.1% hemicellulose and 20.5% of lignin. A high percentage of water absorption of kenaf core (i.e., 50%) was recorded due to the presence of a large number of pits along the longitudinal axis of the cell wall as shown by pictures from SEM. The core fibres has low Runkel ratio of 0.36 which is responsible for high water absorption owing to large lumen size and thin fibre wall suggesting good liquid transmission. Carboxymethylated kenaf core was successfully produced under heterogeneous condition by reacting the core fibres with sodium monochloroacetate as an etherifying agent and isopropanol as reaction medium in the presence of sodium hydroxide as a swelling agent. Several factors affecting the carboxymethylation process such as time, sodium hydroxide concentrations and temperature were studied. The degree of substitution (DS), reaction efficiency (RE) and weight percent gain (WPG) were also determined. Among the three types of kenaf core used, crude kenaf core (CKC), extractive-free kenaf core (KCFE), and extractive- and lignin-free kenaf core (KCFL), KCFL gives the highest DS value. The purity of the holocellulose was found to be the crucial factor in obtaining high yield. The optimum reaction condition for producing carboxymethylated kenaf core with DS value of 0.87 was based on the following procedures: firstly, by extracting the extractives and lignin from the kenaf core to produce extractive- and ligninfree kenaf core (KCFL) and then reacting the KCFL with sodium monochloroacetate in 30% sodium hydroxide at 55oC for 2 hours. From FTIR spectroscopy analysis, the existence of peak at 1591 cm-1 on modified kenaf core revealed that some of hydroxyl groups of cellulose kenaf fibre had been effectively substituted with the carboxymethyl group. The SEM micrograph observation also reconfirmed the substitution process, where the unmodified kenaf core had rough features with the pits still empty. On the other hand, smoother features were observed on the modified kenaf core fibre with the pits has been filled presumably with carboxymethyl of sodium monochloroacetate. Hydrogels were successfully produced using different concentrations of carboxymethylated kenaf core of extractive- and lignin-free (CMKCFL) at several irradiation doses. A dose of 70 kGy was found to be the optimum irradiation dose for crosslinking of CMKCFL hydrogel with gel content of 37.1%. The optimum crosslinking condition was 50 kGy irradiation and 50% concentration, producing an acceptably good properties CMKCFL hydrogel. The swelling ratio of CMKCFL hydrogel was the highest in de-ionized water compared to alkaline (1.0 M NaOH) and acidic (1.0 M HCl) at all ranges of irradiation doses except for 10 kGy. Increasing the level of concentration of aqueous CMKCFL resulted in an increased in swelling. This result was however opposite when the swelling test was conducted in acid and alkali mediums. The overall results indicate that kenaf core fibre can be used as raw material for carboxymethyl cellulose and hydrogel production and possess satisfying other properties.